2019
DOI: 10.4049/jimmunol.1801489
|View full text |Cite
|
Sign up to set email alerts
|

Impact of KIR/HLA Incompatibilities on NK Cell Reconstitution and Clinical Outcome after T Cell–Replete Haploidentical Hematopoietic Stem Cell Transplantation with Posttransplant Cyclophosphamide

Abstract: Little is known regarding the effect of KIR/HLA incompatibilities (inc.) in the setting of T-replete haploidentical allogeneic hematopoietic stem cell transplantation using posttransplant cyclophosphamide (PTCy). In this retrospective study, the impact of KIR/HLA inc. on clinical outcomes and NK cell reconstitution was studied in a cohort of 51 consecutive patients receiving a T cell–replete haploidentical allogeneic hematopoietic stem cell transplantation after a reduced-intensity conditioning using periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 36 publications
1
56
0
2
Order By: Relevance
“…Moreover, the potency of the relapse protection positively correlated with the number of receptor-ligand mismatch pairs ( 39 ). Subsequently, the protective effect of receptor-ligand mismatch has been confirmed by many investigations ( 58 , 59 , 66 , 69 , 71 , 73 , 76 , 79 , 80 ). Moreover, a survival advantage was also observed in patients with receptor-ligand mismatch compared with receptor-ligand matched pairs ( 59 , 66 , 69 71 , 73 , 76 , 79 ).…”
Section: Kir and Transplant Outcomesmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, the potency of the relapse protection positively correlated with the number of receptor-ligand mismatch pairs ( 39 ). Subsequently, the protective effect of receptor-ligand mismatch has been confirmed by many investigations ( 58 , 59 , 66 , 69 , 71 , 73 , 76 , 79 , 80 ). Moreover, a survival advantage was also observed in patients with receptor-ligand mismatch compared with receptor-ligand matched pairs ( 59 , 66 , 69 71 , 73 , 76 , 79 ).…”
Section: Kir and Transplant Outcomesmentioning
confidence: 81%
“…The majority of studies did not report a significant association between these parameters ( 41 44 , 46 , 47 , 50 , 51 , 54 56 , 59 , 65 , 66 , 79 , 81 , 83 , 87 89 , 91 93 , 97 , 98 , 102 , 104 ), while some reported a protective effect ( 70 , 74 , 76 ). Moreover, several studies found that KIR ligand mismatch or receptor-ligand mismatch increased the risk of GVHD ( 45 , 57 , 60 , 64 , 68 , 80 ). Accordingly, two studies performed in China that applied the ‘Peking protocol’ for HSCT using the granulocyte-colony stimulating factor (G-CSF)-mobilized graft containing a high dose of T cells observed promotive effects of NK cell alloreactivity on GVHD ( 48 , 49 ).…”
Section: Kir and Transplant Outcomesmentioning
confidence: 99%
“…We hypothesized that this might promote improved engraftment, maintain the low GVHD and NRM rates inherent in this regimen, and augment NK cell-mediated cytotoxicity, which is believed to be important in HIDT-associated GVM effects. [24][25][26] Although the study failed to meet our statistically predefined goal of decreasing relapse risk, it did show durable engraftment in all patients, which was unexpected, given the historical experience of 10% graft failure with NMA HIDT-PTCy and a PBSC graft. Furthermore, NRM was low (12% at 3 years posttransplant) confirming the safety of this regimen.…”
Section: Discussionmentioning
confidence: 93%
“…Phenotypic analysis of NK cell repertoire reconstitution suggested that alloreactive NK cells can be activated and proliferate, but become particularly targeted by PTCy. She discussed the hypothesis that this activated context might promote the differentiation/activation of NK cells associated with GvL . Lena‐Marie Martin evaluated the relevance of maternal fetal microchimerism (FM) as donor criteria to select optimal haploidentical donor to cure pediatric leukemic patients.…”
Section: Kir and Transplantationmentioning
confidence: 99%